Hepatoprotective properties of Dandelion: recent update - Ezhilarasan Devaraj (Journal of Applied Pharmaceutical Science, 2016)
Taraxacum officinalis (Dandelion) have been used as folk medicines in China, India, and Russia for the treatment of chronic liver diseases. This review focuses exclusively on published literature pertaining to the potential use of Taraxacum officinalis or Dandelion for the treatment of various chronic liver diseases. Dandelion has been tested against various drugs and chemical induced chronic liver diseases in experimental animals and came out with promising results. In vitro studies also confirm the hepatoprotective, antioxidant and anti-inflammatory properties of dandelion. The extensive literature survey reveal the fact that Taraxacum officinalis or dandelion to be safe and the available evidence on the mechanisms of action appears promising, there are currently insufficient data from well-conducted clinical trials to recommend it use in patients with alcoholic liver chronic liver disease.
Keywords: Taraxacum officinale, oxidative stress, antioxidant, hepatoprotective.